2016
DOI: 10.1093/aesa/saw029
|View full text |Cite
|
Sign up to set email alerts
|

Redescriptions of ThreeNasutitermesSpecies (Isoptera: Termitidae: Nasutitermitinae) Occurring in Taiwan

Abstract: Three termite species currently placed into Nasutitermes Dudley, 1890 (Isoptera: Termitidae), occurring in Taiwan, N. kinoshitai (Hozawa, 1915), N. parvonasutus (Nawa, 1911), and N. takasagoensis (Nawa, 1911), are redescribed and keyed. The soldier and worker castes of N. kinoshitai are described for the first time. Neotypes are designated for N. parvonasutus and N. takasagoensis. Significant difference in their morphology and gene sequences of mitochondrial 16S rRNA and internal transcribed spacer (ITS) indic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…The identification of Na. takasagoensis was based on taxonomic description of Liang and Li (2016), and the identification of other termite species was carried out using the systematic key of termites in Thailand (Ahmad 1965, Sornnuwat et al 2004). The nest types were recorded for each termite species were recorded based on observations or reference (Table 1).…”
Section: Study Sites and Termitesmentioning
confidence: 99%
“…The identification of Na. takasagoensis was based on taxonomic description of Liang and Li (2016), and the identification of other termite species was carried out using the systematic key of termites in Thailand (Ahmad 1965, Sornnuwat et al 2004). The nest types were recorded for each termite species were recorded based on observations or reference (Table 1).…”
Section: Study Sites and Termitesmentioning
confidence: 99%
“…Montomery (Montgomery, 1985 ) and Lubin and Montgomery ( 1981 ) reported that Nasutitermes termites are an important part of the diets of both tamandua species. Nasutitermes parvonasutus are commonly found in suburban Taiwan (Liang & Li, 2016 ) and were the species of which the southern tamandua in this study consumed the most. Although N .…”
Section: Discussionmentioning
confidence: 65%
“… Note : * = major workers. References used: [a] Gallo et al, 2017 ; [b] Liang & Li, 2016 ; [c] Lubin et al, 1977 ; [d] Lubin & Montgomery, 1981 ; [e] Montgomery & Lubin, 1977 ; [f] Navarrete & Ortega, 2011 ; [g] Oyarzun et al, 1996 ; [h] Sandoval‐Gómez et al, 2012 . …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations